Characteristics of Helium Gas with High Temperature and High Pressure Flowing through a 90-Degree Elbow. (14th April 2014) - Feng, Beibei; Sun, Yanfei; Yang, Xingtuan; Li, Shengqiang; Tu, Jiyuan; Jiang, Shengyao
Abstract : There exists a certain 90° elbow structures in the helium circulation of HTGR-10. In terms of energy-saving and design simplification of reactor's primary loop, 90° elbow can be used to measure the helium flow and the content of water vapor, both of which are significant in an accident. It is necessary to make an in-depth research of the flow characteristics of helium flowing 90° elbow. Simulation results indicate that fluid's motion in the elbow is under the control of the centrifugal forces. Static pressure near the extrados is higher than that near the intrados. Boundary layer separation occurs at the latter half intrados of the elbow. The vortex emerges during the separation process and increases the energy dissipation. Velocity in the near-intrados region is higher than that in the near-extrados region, which is opposite to the pressure distribution trend. Under the action of the centrifugal forces, the secondary flow emerges in the latter half of the elbow and complicates the flow field by generating two vortexes which rotate in a different direction.